Visual Distraction: An Altered Aiming Spatial Response in Dementia - Galletta, Elizabeth E.; Lequerica, Anthony H.; Pekrul, Scott R.; Eslinger, Paul J.; Barrett, Anna M. (Dementia and geriatric cognitive disorders extra, 2012)
Background/Aims: Healthy individuals demonstrate leftward bias on visuospatial tasks such as line bisection, which has been attributed to right brain dominance. We investigated whether this asymmetry occurred in patients with probable dementia of the Alzheimer type (pAD) which is associated with neurodegenerative changes affecting temporoparietal regions. Methods: Subjects with pAD and matched controls performed a line bisection task in near and far space under conditions of no distraction, left-sided visual distraction and right-sided visual distraction. Results: Participants with pAD manifested different motor-preparatory ‘aiming’ spatial bias than matched controls. There were significantly greater rightward ‘aiming’ motor-intentional errors both without distraction and with right-sided distraction. Conclusion: ‘Aiming’ motor-preparatory brain activity may be induced by distraction in pAD subjects as compared to typical visual-motor function in controls.